1997
DOI: 10.1038/sj.leu.2400871
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and phenotypic analysis of early hematopoietic progenitor cells in umbilical cord blood

Abstract: Umbilical cord blood (UCB) is an attractive potential alternative to bone marrow (BM) as a source of hematopoietic progenitor cells since the number of progenitors in UCB is similar or even greater than that in normal BM. It was the aim of the present study to analyze the degree of immaturity of UCB progenitor cells. UCB mononuclear (MNC) and/or CD34 + cells were tested for surface antigen phenotype, expression of cytokines receptor, effect of stem cell factor (SCF) on colony growth, resistance to mafosfamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Later on, spleen and, predominantly, fetal liver are organs of hematopoiesis before the bone marrow starts to play a leading role (20). Umbilical cord blood contains many hematopoietic progenitor cells (21)(22)(23). In agreement with the higher ex vivo proliferative potential of purified progenitor cells from cord blood compared with adult bone marrow (24), significantly longer telomeres have been observed in umbilical cord blood (14).…”
supporting
confidence: 56%
“…Later on, spleen and, predominantly, fetal liver are organs of hematopoiesis before the bone marrow starts to play a leading role (20). Umbilical cord blood contains many hematopoietic progenitor cells (21)(22)(23). In agreement with the higher ex vivo proliferative potential of purified progenitor cells from cord blood compared with adult bone marrow (24), significantly longer telomeres have been observed in umbilical cord blood (14).…”
supporting
confidence: 56%
“…1,2 However, several phenotypic and functional differences between hematopoietic stem cells from these three tissues have been described during the last few years. [3][4][5][6] The CD34…”
mentioning
confidence: 99%
“…Timeus et al (9) observed that the number of CD34 + CD38 -cells was significantly higher in cord blood than in bone marrow (16 ± 8.8 and 4.7 ± 3% of total CD34 + cells, respectively). However, the number of CD38 -cells among HUCB CD34 + cells was reported as 11% (18), or 34.9 ± 3.4% (20).…”
Section: Discussionmentioning
confidence: 99%